2019
DOI: 10.1007/s40801-019-00161-y
|View full text |Cite
|
Sign up to set email alerts
|

Serious Cardiovascular Adverse Events Reported with Intravenous Sedatives: A Retrospective Analysis of the MedWatch Adverse Event Reporting System

Abstract: Background Serious cardiovascular adverse events (SCAEs) associated with intravenous sedatives remain poorly characterized. Objective The objective of this study was to compare SCAE incidence, types, and mortality between intravenous benzodiazepines (i.e., diazepam, lorazepam, and midazolam), dexmedetomidine, and propofol in the USA over 8 years regardless of the clinical setting where it was administered. Methods The Food and Drug Administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
1
6
1
Order By: Relevance
“…However, the significant increase in the risk for serious AEs was not observed for fentanyl (p > 0.05), which is another primary sedative in a comparable therapeutic place to propofol (Table 4), suggesting a truly high risk of propofol for serious sedative-induced AEs such as cardiovascular events. In fact, similar to our current study, a previous study conducted by Duprey and colleagues reported an increased risk of serious cardiovascular AEs associated with propofol compared to other sedatives [30].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the significant increase in the risk for serious AEs was not observed for fentanyl (p > 0.05), which is another primary sedative in a comparable therapeutic place to propofol (Table 4), suggesting a truly high risk of propofol for serious sedative-induced AEs such as cardiovascular events. In fact, similar to our current study, a previous study conducted by Duprey and colleagues reported an increased risk of serious cardiovascular AEs associated with propofol compared to other sedatives [30].…”
Section: Discussionsupporting
confidence: 91%
“…In our current study, serious events accounted for 3.3% (n = 3132) of the total sedativeinduced AEs, suggesting a substantially lower reporting rate of serious events compared to that in the United States (16.9%) [30]. This might be associated with the reporting pattern of ADEs in Korea [31].…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Midazolam is the sedative of choice for radiographic studies because of its rapid onset of action and short elimination half-life [12] . However, this sedative could be the reason for cardiac arrest in a small proportion of cases [13] .…”
Section: Discussionmentioning
confidence: 99%